Opanowani syndromem konsumpcyjnym? Testowanie koncepcji Zygmunta Baumana - komunikat z badań = Dominated by the consumerist syndrome? Testing Zygmunt Bauman`s concept - research results - Marciniak, Mateusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The objective of the paper is to attempt to answer the question about the extent to which Bauman`s diagnosis (according to which modern humans - members of a consumer society - are dominated by the consumerist syndrome) suits the realities of Polish society.
Keywords: Bauman, Zygmunt (1925-2017); syndrom konsumpcyjny; społeczeństwo płynnonowoczesne